2001
DOI: 10.1002/1529-0131(200103)44:3<561::aid-anr104>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Shift toward T helper 1 cytokines by type II collagen-reactive T cells in patients with rheumatoid arthritis

Abstract: Objective To investigate the impact of type II collagen (CII)–reactive T cells on the Th1/Th2 cytokine balance in patients with rheumatoid arthritis (RA). Methods T cell proliferative responses to bovine CII were examined in synovial fluid mononuclear cells (SFMC) and peripheral blood mononuclear cells (PBMC) by mixed lymphocyte culture. CII‐reactive T cell lines were generated from the SFMC and PBMC. Interferon‐γ (IFNγ), interleukin‐12 (IL‐12), and IL‐4 were measured by enzyme‐linked immunosorbent assay in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…T helper 1 (Th1) and CD8? T cells are reported to be involved in RA pathogenesis [15][16][17]. When triggered by antigenic peptides such as CII, a major component of hyaline cartilage acting as an auto-antigen in RA [18,19], T cells stimulate monocytes, macrophages, and synovial fibroblasts to secrete proinflammatory cytokines such as TNF-a [16].…”
Section: Discussionmentioning
confidence: 99%
“…T helper 1 (Th1) and CD8? T cells are reported to be involved in RA pathogenesis [15][16][17]. When triggered by antigenic peptides such as CII, a major component of hyaline cartilage acting as an auto-antigen in RA [18,19], T cells stimulate monocytes, macrophages, and synovial fibroblasts to secrete proinflammatory cytokines such as TNF-a [16].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated T helper 1 (Th1) responses in draining lymphnodes and arthritis joints of CIA-induced C57BL/6 mice It has been suggested that RA is mediated by IFN-c-producing Th1 cells, which stimulate inflammatory responses. 8,9 It is also reported that Th1 responses are predominant in DLN of CIA-induced mice of DBA/1 background at the time of onset of arthritis. 10 To examine whether Th1 cells are predominant also in CIA-induced C57BL/6 mice, DLN cells were isolated from mice with CIA induced by CII in CFA containing 5 mg/ml of M. tuberculosis or control mice that were immunized with CII in IFA 10 days after the second immunization and were examined for cytokine production by quantitative reverse transcription (RT)-PCR.…”
Section: Induction Of Cia In Mice Of C57bl/6 Backgroundmentioning
confidence: 95%
“…An explanation might be found in recent studies from human patients with RA studying paired PBMC and synovial fluid mononuclear cells (SFMC) samples cultured with collagen type II. These studies demonstrated that the T-lymphocyte responses were more frequent and vigorous in SFMC than in PBMC (Kim et al, 1999;Park et al, 2001;Kim and Kim, 2005) which might suggest that these collagen-specific T-lymphocytes home to joints. We have not investigated SFMC reactivity to collagen type I in this study, however, it would be worthwhile to test this concept in the future as it could result in a clearer differentiation of the immune response in dogs that will sustain a CrCL rupture in their contralateral stifle joint and dogs that will not.…”
Section: Discussionmentioning
confidence: 90%